Unleashing Student Potential: Enhancing Creativity and Performance with Project-Based Learning - Widodo, J. Priyanto (Fakultas Seni Rupa dan Desain ITB, 2024)
The study aims to address the gap in understanding the effectiveness of project-based learning (PjBL) in enhancing students' creativity and academic performance. Despite increasing interest in PjBL, there is a need to thoroughly examine its alignment with traditional instructional paradigms. The study uses a quasi-experimental method design, stratifying participants into an experimental group and a control group. The experimental arm undergoes a targeted PjBL approach, diverging from the control group, which adheres to conventional teaching methodologies. Over a 12-week duration, data is methodically amassed through pre- and post-tests, encapsulating both quantitative and qualitative metrics to evaluate student performance and ingenuity. Preliminary findings underscore a marked enhancement in both creative output and academic performance among students exposed to PjBL. Nonetheless, the study elucidates potential challenges, such as resource constraints and implementation hurdles, necessitating further elucidation. The study suggests that PjBL can enhance students' creative thinking and academic achievement by inducing innovation, problem-solving skills, and collaboration. Future research should explore its impact on student motivation, engagement, and academic success, as well as its adoption and scalability strategies.